Sunitinib in the Treatment of Thyroid Cancer - Ferrari, Silvia M.; Centanni, Marco; Virili, Camilla; Miccoli, Mario; Ferrari, Paola; Ruffilli, Ilaria; Ragusa, Francesca; Antonelli, Alessandro; Fallahi, Poupak (Current Medicinal Chemistry, 2019)
Background: Sunitinib (SU11248) is an oral multi-target tyrosine kinase inhibitor (TKI) with low molecular weight, that inhibits platelet-derived growth factor receptors (PDGF-Rs) and vascular endothelial growth factor receptors (VEGFRs), c-KIT, fms-related tyrosine kinase 3 (FLT3) and RET. The concurrent inhibition of these pathways reduces tumor vascularization and causes cancer cell apoptosis, inducing a tumor shrinkage. Sunitinib is approved for the treatment of imatinib-resistant gastrointestinal stromal tumor (GIST), renal carcinoma, and pancreatic neuroendocrine tumors. Methods: We searched the literature on PubMed library. Results: In vitro studies showed that sunitinib targeted the cytosolic MEK/ERK and SAPK/JNK pathways in the RET/PTC1 cell inhibiting cell proliferation and causing stimulation of sodium/iodide symporter (NIS) gene expression in RET/PTC1 cells. Furthermore sunitinib is active in vitro and in vivo against anaplastic thyroid cancer (ATC) cells. Most of the clinical studies report that sunitinib is effective as first- and second-line TKI therapy in patients with advanced dedifferentiated thyroid cancer (DeTC), or medullary thyroid cancer (MTC). Sunitinib 37.5 mg/day is well tolerated, and effective. The most common adverse events include: reduction in blood cell counts (in particular leukocytes), hand-foot skin reaction, diarrhea, fatigue, nausea, hypertension, and musculoskeletal pain. Conclusion: Even if sunitinib is promising in the therapy of differentiated thyroid carcinoma (DTC), until now no phase III studies have been published, and additional prospective researches are necessary in order to evaluate the real efficacy of sunitinib in aggressive thyroid cancer.
Keywords: thyroid